Prevalence and determinants of pathological internet use among undergraduate students in a public university in Malaysia - Tong, Wen Ting; Islam, Md Ashraful; Low, Wah Yun; Choo, Wan Yuen; Abdullah, Adina (Behavioral Science Research Institute, Srinakharinwirot University, 2019)
Pathological Internet Use (PIU) affects one's physical and mental health, and university students are at risk as they are more likely to develop PIU. This study determines the prevalence of PIU and its associated factors among students in a public university in Malaysia. This cross-sectional study was conducted among 1023 undergraduate students in 2015. The questionnaire comprised of items from the Young's Diagnostic Questionnaire to assess PIU and items related to socio-demography, psychosocial, lifestyle and co-morbidities. Anonymous paper-based data collection method was adopted. Mean age of the respondents was 20.73 ± 1.49 years old. The prevalence of pathological Internet user was 28.9% mostly Chinese (31%), 22 years old and above (31.0%), in Year 1 (31.5%), and those who perceived themselves to be from family from higher socio-economic status (32.5%). The factors found statistically significant (p < 0.05) with PIU were Internet use for three or more hours for recreational purpose (OR: 3.89; 95% CI:1.33 - 11.36), past week of Internet use for pornography purpose (OR: 2.52; 95% CI:1.07 - 5.93), having gambling problem (OR: 3.65; 95% CI:1.64 - 8.12), involvement in drug use in the past 12 months (OR: 6.81; 95% CI:1.42 - 32.77) and having moderate/severe depression (OR: 4.32; 95% CI:1.83 - 10.22). University authorities need to be aware of the prevalence so that interventions can be developed to prevent adverse outcomes. Interventions should focus on screening students for PIU, creating awareness on the negative effects of PIU and promoting healthy and active lifestyle and restricting students' access to harmful websites. © Behavioral Science Research Institute.